Los aplicativos en tepehuano del sureste (o’dam) y tepehuano del suroeste (audam) - Everdell, Michael; García Salido, Gabriela (El Colegio de México, A.C., 2023)
We compare the productive functions of the cognate applicative suffixes in the Southern Tepehuan languages O’dam (-dha y -tuda) and Audam (-dha y -tugda) from a typological perspective. We find that both suffixes in both languages can license subjects and objects, although their specific function is lexically selected by a given verbal stem. The most productive type of sub-ject licensing is causative agents, we additionally find a split in the two suf-fixes in terms of the volitionality of the patient, the volitionality distinction is consistent between Audam -dha and -tugda, while O’dam’s suffixes do not make a consistent distinction. Licensed objects are generally promoted non-arguments and beneficiaries, which are not entailed by the base form of the verb. O’dam shows a much wider range of functions for object licensing. For Audam, argument promotion is a marginal function and O’dam is the only one of the two languages that license the full range of benefactive types.